Order effects when using Hopkinson’s multiple criterion scale of discomfort due to glare - Kent, Michael G.; Fotios, S.; Altomonte, Sergio (Elsevier, 2018)
Hopkinson’s multiple criterion scale is widely used to investigate the subjective degree of discomfort due to glare. Using an adjustment procedure, glare source luminance is adjusted to reveal four levels of discomfort, typically: just imperceptible, just acceptable, just uncomfortable, and just intolerable. In many studies, observers are instructed to attend to each level of discomfort in ascending order, from the lowest to the highest criterion. It is likely, however, that any settings made using this approach are influenced by an order bias, and this would affect the reported thresholds of discomfort. To investigate order effects, a Hopkinson-like multiple criterion adjustment experiment was performed, but under three different order sequences: ascending, descending, and randomised. The results revealed substantial bias due to order effects, particularly for lower glare criteria. This demonstrates the need for caution when interpreting subjective evaluations of discomfort due to glare and estimating the robustness of glare indices derived from studies that used Hopkinson’s scale and procedure.